PEMBINAAN AKHLAK SISWA BERKEBUTUHAN KHUSUS MELALUI KEGIATAN EKSTRAKURIKULER PAI DI SDLB ISLAM YASINDO MALANG - Hasanah, Siti Ma’rifatul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
This article describes the process of implementing the Overlapping Yasindo Islamic SDLB, using a qualitative approach and type of case study research. Sources of data come from informants and documentation tailored to the focus of research. For data collection techniques using interviews, observation and literature studies. The data analysis is done by reducing data, presenting/displaying data and drawing conclusions. To check the validity of the data is done by triangulation of sources and methods, as well as discussions.The results of the study show that: 1). PAI extracurricular activities carried out at Yasindo Islamic Elementary School Malang include daily programs including 4S (Smiles, greetings, and greetings), praying together, reciting the shahada and daily prayers before starting the lesson and after the experience is finished, the Dhuha prayer in congregation, mauidah hasanah, religious knowledge quiz, reciting the Qur'an, memorizing short letters, PHBI (Mawlid Prophet and Muharram 1 st Warning) PHBN (Commemoration of independence and other national holidays). 2) The moral development activities in the Yasindo Islamic SDLB Malang are conducted in 3 stages, the stage of strengthening the concept of morality (knowing), the application stage (doing) The step of being (being) and the creation of a religious atmosphere. 3). Supporting factors in the extracurricular implementation of PAI at Yasindo Malang Islamic SDLB include; active participation and enthusiasm of students, Collaboration with all teachers, support of student guardians, funding from schools, support from all parties. The inhibiting factor includes; The diverse needs of students so that the teacher must pay attention to each, facilities and infrastructure specifically for children with special needs that are less supportive.